Lengthwise Crack Study of a Beam with Non-Linear Creep - Victor Iliev RIZOV (Engineering Transactions)
An analytical study of the strain energy release rate for an inhomogeneous beam structure with a lengthwise crack subjected to non-linear creep is developed. The beam is inhomogeneous along its length. Two cases are analysed (material with identical creep behaviour in tension and compression, and material with asymmetrical creep behaviour). Since the stress cannot be determined explicitly from the non-linear stress-strain-time relationship, an approach for obtaining of time-dependent solutions of the strain energy release rate is developed by expressing the z-coordinate as a function of the stress. The analysis indicates that the asymmetrical creep behaviour leads to an increase in the strain energy release rate.